Study of the Biological Activity of Melanoma-cells on a Culture Medium by Means of the Biospeckle Technique - Martínez-Celorio, R A; González-Peña, R J; Cibrián, R M; Salvador, R; Gil-Benso, R; San Miguel, T; Sánchez-Muñoz, O L (Revista Mexicana de Ingenieria Biomedica, 2012)
We are reporting a study of the response of a biological tissue with a malignant melanoma induced of the cell line MEL-RC08 by means of Biospeckle's technique. The study was performed on four prepared samples, which were placed in plastic wells prepared for such purposes. The used samples were: RPMI-1640 Gel; RPMI-1640 plus 105 cells of the cell line MEL-RC08, and the other two plastic wells was added a concentration of 1 μg and 2 μg of Colcemid drug, respectively. The samples were tested at the same time by analyzing the temporal evolution of speckle patterns in each of them. For that, we designed an experiment, which consisted of to illuminate the samples with an He-Ne laser and acquire a set of 96 images for 24 hours by using a high resolution camera. Next, a temporal difference method for processing dynamic speckle patterns was implemented with the aim of analyzing the biological activity. The obtained results show that exist a change in the behavior of the biological activity of the samples depending on concentration of the applied drug. The advantages and disadvantages of the method are discussed.